A study of job stressors on job satisfaction among investment bankers - Puvana, Marimuthu (2020)
This study has been conducted to examine on the issue faces by the employees who worked in an investment bank, especially factors that influenced their job satisfaction level. The key persistence of this study was identifying the influence of role ambiguity, role conflict, pay and benefits on Job satisfaction. This study was conducted by using quantitative method in which data was collected using a set of questionnaire. The sample of this study comprised of all employees who worked in the Transaction Management Department in an investment bank in Kuala Lumpur, Malaysia. A total of 173 respondents from Transaction management Department took part in this survey. The findings of this study shows there is significant relationship between the Independent (i.e. role conflict, role ambiguity, and pay and benefits) and dependant (i.e. job satisfaction) variables.